Floating Offshore Wind Energy The Next Generation of Wind Energy - Cruz, Joao; Atcheson, Mairead (Green Energy and Technology, 2016)
This book provides a state-of-the-art review of floating offshore wind turbines (FOWT). It offers developers a global perspective on floating offshore wind energy conversion technology, documenting the key challenges and practical solutions that this new industry has found to date. Drawing on a wide network of experts, it reviews the conception, early design stages, load & structural analysis and the construction of FOWT. It also presents and discusses data from pioneering projects. Written by experienced professionals from a mix of academia and industry, the content is both practical and visionary. As one of the first titles dedicated to FOWT, it is a must-have for anyone interested in offshore renewable energy conversion technologies.